A Bird’s Eye View of the Systematics of Convolvulaceae: Novel Insights From Nuclear Genomic Data - Simões, Ana Rita G.; Eserman, Lauren A.; Zuntini, Alexandre R.; Chatrou, Lars W.; Utteridge, Timothy M. A.; Maurin, Olivier; Rokni, Saba; Roy, Shyamali; Forest, Félix; Baker, William J.; Stefanović, Saša (Frontiers in Plant Science, 2022)
Convolvulaceae is a family of c. 2,000 species, distributed across 60 currently recognized genera. It includes species of high economic importance, such as the crop sweet potato (Ipomoea batatas L.), the ornamental morning glories (Ipomoea L.), bindweeds (Convolvulus L.), and dodders, the parasitic vines (Cuscuta L.). Earlier phylogenetic studies, based predominantly on chloroplast markers or a single nuclear region, have provided a framework for systematic studies of the family, but uncertainty remains at the level of the relationships among subfamilies, tribes, and genera, hindering evolutionary inferences and taxonomic advances. One of the enduring enigmas has been the relationship of Cuscuta to the rest of Convolvulaceae. Other examples of unresolved issues include the monophyly and relationships within Merremieae, the “bifid-style” clade (Dicranostyloideae), as well as the relative positions of Erycibe Roxb. and Cardiochlamyeae. In this study, we explore a large dataset of nuclear genes generated using Angiosperms353 kit, as a contribution to resolving some of these remaining phylogenetic uncertainties within Convolvulaceae. For the first time, a strongly supported backbone of the family is provided. Cuscuta is confirmed to belong within family Convolvulaceae. “Merremieae,” in their former tribal circumscription, are recovered as non-monophyletic, with the unexpected placement of Distimake Raf. as sister to the clade that contains Ipomoeeae and Decalobanthus Ooststr., and Convolvuleae nested within the remaining “Merremieae.” The monophyly of Dicranostyloideae, including Jacquemontia Choisy, is strongly supported, albeit novel relationships between genera are hypothesized, challenging the current tribal delimitation. The exact placements of Erycibe and Cuscuta remain uncertain, requiring further investigation. Our study explores the benefits and limitations of increasing sequence data in resolving higher-level relationships within Convolvulaceae, and highlights the need for expanded taxonomic sampling, to facilitate a much-needed revised classification of the family.